A framework for assessing the relational accessibility of protected areas. (1st September 2018) - Forleo, Maria Bonaventura; Palmieri, Nadia
Abstract: Human - nature relationship concept has recently been reconsidered, emphasizing the benefits humans beings receive from ecosystems. This study moves from the awareness of the importance for organizations that manage protected areas to design strategies and actions aimed at improving the relatedness between the natural world and people, and between individuals. Starting from this premise, the study proposes a voluntary framework of relational accessibility, with the aim of improving the visitor-organization relationship and the human-nature relatedness, and thus creating value for the organizations themselves. After defining the relationship concept, the approach and the content of the framework are set, based on multidisciplinary fields and approaches. The framework follows a cyclical approach and consists of a set of general and specific requirements and guidelines. To support the definition of the framework, relational accessibility is investigated within a specific protected area, through a focus group and a direct survey with children. The framework is then defined in more general terms, so that it can suitable for application to other environmental and organizational contexts. The relational accessibility framework is discussed with the managing board of the study site and compared with other sustainability tools. The implementation of the relational framework within the management system of protected areas could increase the social and economic value of these areas, while at the same time pursuing environmental goals.